Perancangan alat pemotong kayu dengan dua mata pisau menggunakan dinamo sebagai mesin penggerak yang multifungsi - M Miko Mizar; Asnawi Lubis; Tumpal Ojahan Rajagukguk (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
Technology continues to develop all the time along with the progress of the times, in addition to facilitating human work, the use of machines is very helpful in increasing productivity in a relatively faster time, including wood processing craftsmen in Indonesia. To make it easier for wood craftsmen, a modern saw machine is needed so that it is hoped that the demand from the community can be met. This study aims to design a wood cutting tool and find out how long it takes to cut wood with a thickness of 0.75 cm, 1.75 cm, 2.75 cm and 3.75 cm, and a cutting width of 3 cm. The design of this multifunctional tool uses cutting blades and an AC 220 V – 180 watt dynamo as a driving machine. The result of the design is shaped like a table with two blades that can be used interchangeably, and there is sandpaper on the front that functions as a smoothing part of the cut wood. This tool has a height of 90 cm, a width of 50 cm, a length of 70 cm, and the height of the top blade holder is 15 cm, and the top blade holder is 60 cm long, the sandpaper holder is on the front side. This tool is able to cut the type of wood medang aged approximately 15 years in the form of blocks with a thickness of 0.75 cm in 2.51 seconds, 1.75 cm 3.72 seconds, 2.75 cm in 6.27 seconds, and 3. 75 cm with 8.70 seconds average time.